Direct Observation of Myoglobin Structural Dynamics from 100 picoseconds to 1 microsecond with Picosecond X-ray Solution Scattering - Kim, Kyung Hwan (2010)
Here we report structural dynamics of equine myoglobin (Mb) in response to the CO photodissociation visualized by picosecond time-resolved X-ray solution scattering. The data clearly reveals new structural dynamics that occurs in the timescale of ~360 picoseconds (ps) and ~9 nanoseconds (ns), which have not been clearly detected in previous studies.